Characterization of halotolerant Kushneria isolates that stimulate growth of alfalfa in saline conditions - Iqra Farooq; Niaz Ahmad; Cardon Porter; Rachel Smith; Thomas Scharf; Aden Cowley; Andrew Jenkins; Joshua D. Yates; Jonathon T. Hill; Brent L. Nielsen (PLoS ONE, 2025)
A key barrier to crop production is soil salinity, which is a serious and growing problem world-wide due to inadequate water drainage, saline ground water, or inadequate rainfall to wash away soil salts. There is substantial promise for plant-associated microbes isolated from halophytes (salt-tolerant plants) to enhance growth of salt-sensitive crop plants in salty soils. The objective of this study was to identify salt-tolerant bacteria from native halophytes and characterize their ability to stimulate the growth of alfalfa in salty soil conditions. Several halotolerant bacteria, including Kushneria, Halomonas, and Bacillus, were identified from the rhizosphere or roots of three halophyte species (Salicornia rubra, Sarcocornia utahensis, and Allenrolfea occidentalis) in a saline area south of Utah Lake, Utah, USA. Biochemical properties, including indole acetic acid production, biofilm formation, phosphate solubilization and siderophore production activities, which have been associated with plant growth promoting (PGP) activity, were characterized for several isolates. Selected strains were screened for the ability to stimulate growth of alfalfa in controlled laboratory experiments. Among these strains, two independent isolates of the genus Kushneria were found to have significant growth-promoting activity for inoculated alfalfa plants grown under saline conditions (0.205 M or 1.2% NaCl) that mimic common salinity levels of affected soils. Plants inoculated with a combination of two Kushneria strains that have salt-tolerant PGP (ST-PGP) properties exhibited a statistically significant increase in plant growth over uninoculated plants. A GFP marker confirmed presence of Kushneria in the roots of inoculated plants. Bacteria with ST-PGP activity will be a key resource to facilitate increased crop yield from land affected by salinity, and the data presented here for two Kushneria isolates are promising.